Non-Neoplastic Testicular and Paratesticular Lesions: Study from A Remote Indian Island - Gargade, Chitrawati Bal; Deshpande, Archana Hemant (Annals of Pathology and Laboratory Medicine, 2020)
Background: Testicular and paratesticular lesions can represent a wide range of medical issues, from benign congenital conditions to life threatening malignancies and acute surgical emergencies. Most of the studies are done about the testicular tumors and very little literature is available about non-neoplastic lesions of testis and paratesticular tissue. Hence present study was undertaken to know the histomorphologic spectrum of nonneoplastic testicular and paratestesticuar lesions. Methods: This is a prospective study done over a three year period from Jan 2016 to Jan 2019 includes orchidectomy specimens and paratesticular tissue received for histopathological examination in the Department of Pathology of a newly established medical college on a remote Indian Island. Result: Total 51 orchidectomy specimens and two paratesticular tissues are received for histopathological examination. Out of 51 orchidectomy specimens; non neoplastic testicular lesions (94.1%) were far more common than neoplastic lesions (5.9%). The most common non-neoplastic testicular lesion was torsion testis (19/48=39.6%) and most cases were seen in first two decades. The youngest patient was 11 months and oldest was 42 years of age. Long standing hydrocele, Pyocele and haematocele were the second most common cause for orchidectomy, in forty plus age group. Undescended testis as cause comprised 7.6% of the total orchidectomy specimens. One case of Epididymal cyst was found. Two paratesticular tissues received. One specimen showed appendix of testis and was cause of recurrent epididymo- orchitis in 11 yrs old boy. Gubernaculum was found in another specimen in a case of vanishing testis syndrome. Neoplasms formed a miniscule proportion – only three cases were diagnosed. Conclusion: Nonneoplastic lesions are more common than neoplastic lesions. Torsion testis was the commonest indication for orchidectomy in younger age group while hydrocele, pyocele and chronic haematocele were the common causes in older patients. Appendixes of testis, gubernaculum of vanishing testis, epididymal cyst as non-neoplastic paratesticular lesions found in few cases.